DESAIN SUPERBLOK MIXED USE (APARTEMEN, MALL, RENTAL OFFICE) DI MEDAN DENGAN KONSEP ARSITEKTUR EKOLOGIS - Muhammad AL Fadli (Arsitektur UMJ, 2019)
Mixed-Superblock in Medan motivated by the potential and high economicattractiveness of Medan but not matched with good urban planning so that Medan is notready to accept urbanization and has residential and transportation issues. The objective ofthis scheme is to get the design of superblock area is able to accommodate business andcommercial activities, supported by residential facilities and access to public transportation. The method is the ecological principles of the planning of buildings and artificial environment. There is a link between the preparation of building planning patterns of local natural conditions Design issues to be resolved are: the selectionand processing footprint suitable for the needs of a superblock, and can support both business and commercial activity as main activity, as well as residential and recreational activities assecondary activities. The results are a design of superblock area is able to accommodatebusiness activities and commercial (work), residential, and recreation with the support ofpublic transportation access with the ecological approach